MENINGKATKAN KREATIVITAS SISWA KELAS 5 DALAM PEMBELAJARAN SENI RUPA SD PADA KEGIATAN P5 DENGAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DI SD NEGERI KUANINO - anthonia, Yayang anastasya angel; Sogen, Yosephina k.; Djokaho, Margaret p.e. (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to improve the creativity of grade V students in learning elementary fine arts in P5 activities with a project-based learning model at SD Negeri Kuanino. This type of research is a class action research with the research subjects are students of class V SD Negeri Kuanino Kupang, totaling 21 people. Data collection through observation techniques and collage making practices. In the pre-cycle research results there were 10 students who completed meeting the KKM with a percentage of completeness of 47.61%. In cycle I the percentage of completeness was 25% and only 1 group reached KKM while in cycle II it increased with a percentage of completeness of 75% or 3 groups that reached KKM. Thus it can be concluded that the Project Based Learning model can increase student creativity in learning fine arts in grade V of SD Negeri Kuanino Kota Kupang.